IS PBL CULTURE FAIR? THE INFLUENCE OF GROUP CULTURAL COMPOSITIONS ON STUDENT PERFORMANCE IN A PROBLEM BASED LEARNING SETTING - SIEHOYONO, LINTJE; ERINGA, KLAAS (ITB Journal Publisher, LPPM ITB, 2005)
This paper reports the result of an exploratory study of the application of Terenzini et al. (2001) and Eringa et al. (2002) to an educational institution, one of the N’etherlands’ higher education in which apply PBL as an educational system. Recently, the International Hospitality Management (IHM) undergraduate program has decided to deploy internationalization and interculturalization as a strategic instrument for the diversification of its curriculum. One of the consequences is that large groups offoreign students have been attracted to the IHM. The purpose of this study is to investigate how the student nationalities and the group cultural compositions in PBL groupsinfluence the student performance. Student performance is measured by learning process assessment (PBL participation points) and learning outcomes assessment (Total points for the module). More specifically, this study focuses on possible cultural bias (nationalities) that might accompany the form of assessment that the IHM uses. The results indicate that no significant differences exist between groups that are more or less divergent.